Competências dos profissionais de secretariado de empresas nacionais, nacionais internacionalizadas e estrangeiras no Brasil - Almeida, Walkíria Aparecida Gomes de (2016)
This research aimed to identify if the international nature of the company influences on the development of the different individual competencies for the secretariat professional. The approach was quantitative and the research methodology was the search of data as well as the technical collect survey. The work has three main stages. On the first we have developed the scale using the literature review. Following, the second stage, there was the choice of ten specialists to the scale validation. On the third, there was the questionnaire preparation according to the validation of experienced professionals. And finally, the last stage there was the questionnaire application for 252 secretariat professionals who attended the International Congress of Secretariat COINS, August, 20 22th, 2015, in the city of Santos São Paulo - Brazil. The results have shown that a part of the ensemble of competencies established by MEC (BRASIL, 2005) is related to the five constructs which were studied on the research: client relationship: quality works searching for the satisfaction of both intern and external clients. Team work: working with other professionals articulating knowledge. Time management: work with planning and delegation. Creativity/innovation: deal with something new or improve the existing work. Negotiation: includes search for results, mutual advantages and better customer relationship which confirms hypothesis 01. As for the behavioral competences it is observed that the professionals mention only four of the competencies studied in the literature review, what confirms hypothesis 02 partially. According to the data hypothesis 03 could not be confirmed, if there is a difference in the set of competencies of the secretariat professional who work in national or international companies. The research points out that the professionals from national and international companies develop similar competencies. We believe that the results presented in this work can contribute to researchers as well as future studies on Secretariat in Brazil and other countries.